Isotopes in Palaeoenvironmental Research - Leng, Melanie J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
This 10th volume in the DPER series is intended to show how stable isotopes can be applied to understanding the palaeoenvironment. There are chapters on the interpretation of isotopes in water, tree rings, bones and teeth, lake sediments, speleothems and marine sediments. Isotopes can be extremely powerful palaeoenvironmental tools, however, as with all archives it is desirable to carry out a calibration exercise to investigate the basic systematics of isotope variation in the modern environment to establish the relationship between the measured signal and the isotope composition of the host. A robust calibration is seldom easy so isotope methods should be used in conjunction with a multi-proxy approach, using isotope signals from different materials or combined with other palaeoenvironmental techniques. This book is advanced but aimed at both students and scientists who are interested in environmental change.
ISOTOPES IN WATER -- ISOTOPES IN TREE RINGS -- ISOTOPES IN BONES AND TEETH -- ISOTOPES IN LAKE SEDIMENTS -- ISOTOPES IN SPELEOTHEMS -- ISOTOPES IN MARINE SEDIMENTS.
Keywords: PALEONTOLOGY; CLIMATIC CHANGES; GEOSCIENCES; CLIMATE CHANGE; GEOSCIENCES, GENERAL; PALEONTOLOGY